2008
DOI: 10.1007/s00253-008-1717-6
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of the resident microbiota in a thermophilic municipal biogas plant

Abstract: Biogas plants continuously convert biological wastes mainly into a mixture of methane, CO2 and H2O-a conversion that is carried out by a consortium of bacteria and archaea. Especially in the municipal plants dedicated towards waste treatment, the reactor feed may vary considerably, exposing the resident microbiota to a changing variety of substrates. To evaluate how and if such changes influence the microbiology, an established biogas plant (6,600 m3, up to 600 m3 biogas per h) was followed over the course of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(56 citation statements)
references
References 33 publications
5
50
0
1
Order By: Relevance
“…(5 0 -TTACCGCGGCTGCTGGCAC-3 0 ) (Delong, 1992;Koike et al, 2007) for bacteria and Arch344F (5 0 -ACGGGGYGCAG- (Weiss et al, 2008) for archaea.…”
Section: High-throughput 454 Pyrosequencingmentioning
confidence: 99%
“…(5 0 -TTACCGCGGCTGCTGGCAC-3 0 ) (Delong, 1992;Koike et al, 2007) for bacteria and Arch344F (5 0 -ACGGGGYGCAG- (Weiss et al, 2008) for archaea.…”
Section: High-throughput 454 Pyrosequencingmentioning
confidence: 99%
“…Olsenellae are found in the healthy (Ozutsumi et al, 2005;Cho et al, 2006;Hernandez et al, 2008) and acidotic (Tajima et al, 2000) bovine rumen. Moleculargenetic studies have also reported the detection of Olsenella-related clones in the gastrointestinal tracts of humans (Martinez-Medina et al, 2006;Khachatryan et al, 2008;Krogius-Kurikka et al, 2009), pigs (Leser et al, 2002;Tsukahara & Ushida, 2002;Dowd et al, 2008), wallabies (Chhour et al, 2008) and chickens (Lu et al, 2003) and in diverse anaerobic environmental sites (Bowman et al, 2006;Wongtanet et al, 2007;Weiss et al, 2008;Rivière et al, 2009). This indicates that the habitats of the olsenellae generally comprise the oral cavity and gastrointestinal tract of homoeothermic vertebrates and that non-animal habitats also exist.…”
mentioning
confidence: 99%
“…OTU ecb9 was classifi ed under the genus Anaerobaculum (Table 1) by the RDP classifi er. Anaerobaculum species have previously been identifi ed as taxa that produce hydrogen anaerobically from a range of substrates along with oxidized carbon, typically in the form of acetate (Maune and Tanner, 2011;Menes and Muxi, 2002;Weiss et al, 2008) and presumably a similar form of oxidized carbon is being produced on the addition of POA2.…”
Section: Results and Discusssionmentioning
confidence: 99%